Formation of a magnetic composite by reduction of Co-Nd doped strontium hexaferrite in a hydrogen gas flow - Herme, Carlos Alberto (2012)
Co-Nd strontium hexaferrite nanoparticles synthesized by the self-combustion method were treated in a hydrogen flow at different temperatures and times. The samples were characterized structurally by scanning electron microscopy and X-ray diffraction and magnetically with a vibrating sample magnetometer. Phase identification showed decomposition of the hexaferrite structure into Fe 3O 4 and different strontium mixed oxides. The sample treated at 500 °C for 30 minutes shows good magnetic properties due to the formation of a magnetite/hexaferrite composite. In this case magnetization is very close to the original sample while the coercivity slightly diminishes. The hexagonal phase is almost completely transformed into different oxides at a reducing temperature of 500 °C for 120 minutes. The obtained results are analyzed in terms of the phase composition and of the magnetic susceptibility of the studied samples.